Perception of Medical Students at Ciputra University Aged 17-25 Years Regarding The Importance of Sunscreen Use - Gumay, Nur Intan Permatasari; Nurhadi, Stefani; Sayogo, William; Wirya, Stephen Akihiro (Open Access Health Scientific Journal, 2025)
Background: The use of  sunscreen is important in the efforts to protect the skin from the dangers of ultraviolet (UV) radiation. Sunscreen contains protective components measured  by sun protection factor (SPF) and UVA protection. The perception of sunscreen use is essential  for maintaining skin  health, especially among medical students who have more excellent knowledge about the harmful effects of UV radiation. Continuous exposure to UV radiation can lead to skin damage, such as sunburn, darkening, the appearance of spots on the face, dullness, premature aging, and even melanoma. This research aimed to provide evaluation, insight, and confidence regarding the importance of sunscreen use. By understanding this perception, it is hoped that we can identify shortcomings in education and develop interventions to promote sunscreen use practices in the broader community.Methods: The research employed a descriptive approach. Data collection was conducted using total sampling techniques with questionnaires distributed to 184 medical students at Ciputra University aged 17 to 25 years.Results: Descriptive tests were performed.Conclusion: Both students who use sunscreen and those who do not express that using sunscreen is important.